A method for quality improvement of waste printed circuit boards based on overall crushing pre-concentration effect. (20th February 2021) - Zhang, Bo; Guo, Junwei; Zhang, Zhenxing; Zhao, Pengfei; Yan, Guanghui
Abstract: In this study, an overall pre-concentration evaluating method, which originates from the dispersion degree between target element and crushed products, was proposed for WPCBs (waste printed circuit boards). The particle size distribution, element distribution and appearance of crushing WPCBs were systematically studied. The combination between this method and traditional evaluating method was conducted. The results show that particle size distribution was greatly affected by the feed volume ratio and crushing time. The metal components were folded or agglomerated and the copper enriched in 0.5–2 mm by crushing. Under this evaluating method, enrichment effect was reflected accurately and the maximum overall pre-concentration index was 0.41 in 90s, 35% feed volume. Under this condition, the highest separation degree of copper and crushed product can be realized, and it is good for subsequent processing and utilization. Graphical abstract: Image 1 Highlights: An overall pre-concentration evaluating method for crushing was proposed. Main treated conditions and the tendency of crushing effect are obtained. The pre-concentration effect of WPCBs is compared between traditional and new evaluating method. The appearance analysis of WPCBs is conducted for crushed products.